2013
DOI: 10.1002/ajpa.22357
|View full text |Cite
|
Sign up to set email alerts
|

Body composition and cardiometabolic disease risk factors in captive baboons (Papio hamadryas sp.): Sexual dimorphism

Abstract: Baboons (Papio hamadryas Sp.) exhibit significant sexual dimorphism in body size. Sexual dimorphism is also exhibited in a number of circulating factors associated with risk of cardiometabolic disease. We investigated whether sexual dimorphism in body size and composition underlie these differences. We examined data from 28 male and 24 female outdoor group-housed young adult baboons enrolled in a longitudinal observational study of cardiometabolic disease risk factors. Animals were sedated with ketamine HCl (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…In addition, a diet high in simple carbohydrates and fat causes baboons to develop increased body fat and TG concentrations, altered adipokine concentrations, and altered glucose metabolism, consistent with observations in humans (Higgins et al 2010). Even on a normal chow diet, some animals develop insulin resistance, dyslipidemia, atherosclerosis, and CVD, recapitulating metabolic complications seen in humans (Higgins et al 2014;Kamath et al 2011;Kulkarni et al 2014).…”
Section: Introductionsupporting
confidence: 71%
“…In addition, a diet high in simple carbohydrates and fat causes baboons to develop increased body fat and TG concentrations, altered adipokine concentrations, and altered glucose metabolism, consistent with observations in humans (Higgins et al 2010). Even on a normal chow diet, some animals develop insulin resistance, dyslipidemia, atherosclerosis, and CVD, recapitulating metabolic complications seen in humans (Higgins et al 2014;Kamath et al 2011;Kulkarni et al 2014).…”
Section: Introductionsupporting
confidence: 71%
“…Given the particular importance of nonhuman primates as translational models for metabolic diseases (7, 40), investigations to confirm that gut-brain and brain-gut signaling pathways found in rodents are operative in nonhuman primates is of considerable importance. The baboon model is well established in the study of all stages of metabolic disease (9,19,25,26,28,46). Our ICV infusion methodology advances previously described ICV infusion techniques applied in conscious nonhuman primates (3,4,43).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, the correlations suggest that circulating leptin, adiponectin, and triglyceride concentrations were more strongly related to %DFAT than to AC. Although we were limited to the use of AC as a measure of whole body adiposity, we have previously shown that AC is a robust predictor of dual-energy X-ray absorptiometry measured body fat in baboons [16,28] as both male and female baboons distribute excess body fat in the abdominal region [15]. However, we have previously shown that whole body fat deposition negatively affects insulin sensitivity determined by the gold standard methodology, the euglycemic clamp as well as indirect measures of insulin sensitivity such as Homa-IR and insulin levels (16,28).…”
Section: Discussionmentioning
confidence: 99%
“…housed at the Southwest National Primate Research Center (SNPRC), San Antonio, TX. Female baboons were studied to avoid the confounding effects of sex differences in adiposity and metabolic disease risk factors [15,16].…”
Section: Nonhuman Primatesmentioning
confidence: 99%